Analisis Komunikasi Efektif Terhadap Capaian Kapitasi Berbasis Kinerja di Fasilitas Kesehatan Tingkat Pertama Kabupaten Bengkayang - Nanda Elok Juwita; Dwi Santoso (BPJS Kesehatan, 2023)
The achievement of Performance-Based Capitation (KBK) at the First Level Health Facility (FKTP) of Bengkayang Regency has increased from June 2020 to June 2023. Of the total 24 FKTPs that work together, there are 13 FKTPs that have achieved 100% KBK. This achievement was obtained through effective communication carried out between BPJS Kesehatan Bengkayang and FKTP. The purpose of this study is to analyze the success of effective communication applied, then associated with the theory of the REACH (Respect, Emphaty, Audible, Clarity, Humble) principles that have been applied and interpersonal communication. The method used was qualitative research in-depth interview, with the informant's selection technique based on the inclusion criteria set by researchers. 13 FKTP leaders and PICs who have 100% KBK as informants were obtained, then used qualitative data analysis from Matthew et al followed by the validity of theoretical triangulation related to the results of interviews with the REACH principle theory and 3 interpersonal communication theories namely Dual Process Theory, Advice Response Theory (ART) and Attachment Theory. The results of the study found important points from the interview including understanding, teamwork, strategy, feedback, openness, attention, responsiveness, support, communicative, friendly, and respect. These important points correspond to the REACH principles and the 3 theories of interpersonal communication analyzed.